2013
DOI: 10.1007/s12687-013-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of inherited neuromuscular disorders due to endogamy in Northeast Brazil: the need of community genetics services

Abstract: The aim of this study was to investigate the prevalence of inherited neuromuscular disorders (NMDs) in eight communities in Northeast (NE) Brazil in which there was an elevated rate of inbreeding. A cross-sectional epidemiological study, using the key informant (KI) approach, was performed to estimate the prevalence of NMD among the 48,499 individuals living in these eight communities, located in the backlands of the Paraíba State. Twenty-seven individuals fulfilled the diagnostic criteria for inherited NMD, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…A population study in northeast Brazil concluded that high rates of endogamy within certain ethnic groups increased the prevalence of NMD. The estimated prevalence of 80 per 100 000 is similar to that found in the South Asian children of Yorkshire, although the Brazilian study looked at the total population …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A population study in northeast Brazil concluded that high rates of endogamy within certain ethnic groups increased the prevalence of NMD. The estimated prevalence of 80 per 100 000 is similar to that found in the South Asian children of Yorkshire, although the Brazilian study looked at the total population …”
Section: Discussionsupporting
confidence: 59%
“…The estimated prevalence of 80 per 100 000 is similar to that found in the South Asian children of Yorkshire, although the Brazilian study looked at the total population. 16 Previous genetic studies within the South Asian Muslim population show that 63% of parents are cousins and that the Pakistani community in West Yorkshire marry within sub-communities known as Biraderi and originate from a small number of ancestral groups. 17,18 High rates of parental consanguinity have been identified in South Asian Pakistani families 13 and were documented in 28.7% of families (all South Asian) in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…A founder effect is very likely for NKH given the high concentration of patients in a narrow geographic area (i.e., Kairouan) and the high rate of endogamy and consanguineous marriages which favor expression of recessive genetic disorders at high rates. 14,15 Such hypothesis could not be confirmed since mutational analyses were not performed in Tunisian NKH patients. In Tunisia, congenital and infantile forms as well as severe phenotype predominated, which agree with literature.…”
Section: Discussionmentioning
confidence: 99%
“…We also would like to address that among our results, SNVs not yet described appear with high frequency in the present cohort, including c.1297G>A, with a frequency of 23.1% in our study. This might be explained by some inbreeding observed in Brazilian Northeast region [43][44][45] and the lack of genetic studies in this region of Brazil. On the other hand, frequency of the SNP rs11676272 in the present study (48.1%) was the same as described in ExAC Browser for the general population (48%) and similar to that observed among individuals with European ancestry (46%).…”
Section: Discussionmentioning
confidence: 99%